2020
DOI: 10.1080/19475683.2020.1754291
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study on the relationship between land surface temperature and land use/land cover indices

Abstract: The present study focuses on the estimating land surface temperature (LST) of Raipur City in India emphasizing the urban heat island (UHI) and non-UHI inside the city boundary and their relationship with normalized difference vegetation index, normalized difference water index, normalized difference built-up index, and normalized multi-band drought index. The entire study has been performed on four multi-date Landsat 8 Operational Land Imager and Thermal Infrared Sensor images taken from four different seasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…With both SAVI and MNDWI bearing a stronger correlation with LST in both the cities, it can be suggested that the impact of UHI is strong in at least over 50% of the areas. Guha et al [81] reported that vegetation areas have a much better negative correlation with LST, but these relationships gradually weaken with the increase of the heterogeneous surface features. Although Panaji has a smaller urban area compared to Tumkur, the large water body, forest cover, and hilly features render Panaji city as a more heterogeneous surface than Tumkur city, which is located in the plains of India's interior.…”
Section: Discussionmentioning
confidence: 99%
“…With both SAVI and MNDWI bearing a stronger correlation with LST in both the cities, it can be suggested that the impact of UHI is strong in at least over 50% of the areas. Guha et al [81] reported that vegetation areas have a much better negative correlation with LST, but these relationships gradually weaken with the increase of the heterogeneous surface features. Although Panaji has a smaller urban area compared to Tumkur, the large water body, forest cover, and hilly features render Panaji city as a more heterogeneous surface than Tumkur city, which is located in the plains of India's interior.…”
Section: Discussionmentioning
confidence: 99%
“…Urban heat island and urban hot spots are a very common term in an urban environment and are indicated by the zone of very high LST inside the urban bodies (Guha et al 2017). Normalized difference water index (NDWI) is the most popular index for water surface extraction and it is invariably used in LULC and LST related studies (McFeeters 1996;Chen et al 2006;Essa et al 2012;Yuan et al 2017;Guha et al 2020b). Generally, the nature of LST-NDWI relationship in an urban area is insignificant which is controlled by several factors, such as humidity, vegetation, wetland, bare land, air pollution, rock surface, dry or wet soil, heterogeneous man-made materials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial variation of LST is mainly due to the variation of the reflectance and roughness of land surface (Grimm et al 2008). Generally, green vegetation and water bodies present low LST, whereas built-up area, bare rock surface, or dry soil reflects high LST (Li et al 2017;Guha et al 2020b;Guha, Govil, and Diwan 2020). Thus, LST related studies are very important in urban and land use planning and development.…”
Section: Introductionmentioning
confidence: 99%